Challenges and innovations in harmonising sharīʿah and modern family law: Malaysia experience - Mohd, Azizah (GCLT (Global Center for Legal Thought), Islamabad, 2024)
Harmonisation of Sharīʿah and civil law particularly in Malaysia is not a new concept. It has existed and ongoing informally in Malaysian Legal system. As Malaysia is practicing dual legal system, i.e. Islamic and civil law, harmonisation of laws seems significant in the sense that both Sharīʿah and civil law are applicable to all Malaysians, Muslims and non-Muslims. This paper seeks to examine challenges and innovations in harmonising Sharīʿah and modern family law particularly in Malaysia being multi-racial country. The paper will address selected family law issues that is deemed harmonised as well as the main challenges and innovations in harmonising several related family law issues that are not deemed harmonised which include matters relating to remedy in breach of betrothal agreement, age of marriage, maintenance of wife and children, child adoption and custody, polygamous marriage, registration of marriage and divorce and one court solution in the case of conversion to Islam. The research adopts qualitative research methodology based in the library It is hoped that this study will provide a useful source of reference to all that seeks understanding and sampling on harmonisation of Sharīʿah and civil law particularly in modern family law.